PENDAPATAN, NILAI TAMBAH, DAN PEMASARAN AGROINDUSTRI TAHU HOUSE OF TOFU DI KOTA BANDAR LAMPUNG - Anis Hasna Syafitri; Wan Abbas Zakaria; Yaktiworo Indriani (Lampung University, 2021)
This study aims to analyze income, added value of tofu soybeans, tofu product marketing channels, and marketing margins. The research method used is the case study method in the Agroindustrial House of Tofu, Way Halim Permai Village, Way Halim District, Bandar Lampung City. The location of the research was determined deliberately with the consideration that Way Halim District is the center of tofu agroindustry in Bandar Lampung City and House of Tofu Agroindustry with the highest production in Way Halim Regency. This research was conducted in January - March 2020. The data analysis method used in this research was qualitative and quantitative descriptive analysis. The results showed that the income of producing each tofu product was profitable because R/C > 1 and the agroindustry had positive added value. The marketing channel consists of three channels. The market share for all types of tofu in the marketing process of the House of Tofu Agroindustry is more than 50%.Key words : agroindustry, income, marketing, production, tofu.